PENGARUH PEMBERIAN PUPUK CAIR LIMBAH BIOGAS DAN PUPUK N, P, K TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI EDAMAME (Glycine max (L) Merill) - Hervina Ramalia; Fetmi Silvina; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Edamame soybean is the plant from Japan. Edamame soybean production has a relatively short lifespan than regular soy because it is harvested when the pods are young. Bioslurry is one of organic material that can be applied as a liquid organic fertilizer on edamame soybean, but the giving of bioslurry only in the short term has not been able to occupied the nutrient requirements for edamame soybean, so it needs the addition of organic fertilizers such as  anorganic fertilizer N, P, K. This study aimed to get the interaction effect of bioslurry and N, P, K fertilizers on the growth and production of edamame soybean (Glycine max (L) Merrill) and get best treatment. This study was a factorial experiment arranged in Randomized Block Design (RBD) consisting of 2 factors and 3 replications. The parameters observed were plant height, percentage of effective root nodules, plant dry weight, days to flowering, number of pods per plant, pod percentage pithy, weight of pods per plant and weight of pods per plot. The results showed that the interaction effect of bioslurry and fertilizer N, P, K did not affected the plant height and days to flowering and affected the percentage of effective root nodules, dry weight of pods per plant, pod percentage pithy weight of pods per plant and weight of pods per plot. Based on the research results of bioslurry application (500 ml /plant) and N, P, K (3.3+ 9.9+8.8)g/plot fertilizers gives the best results on the growth and production of soybean edamame. Keywords: edamame soybean, bioslurry, N, P, K  fertilizer.